2018
DOI: 10.1073/pnas.1700294115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of national ecological restoration projects on carbon sequestration in China from 2001 to 2010

Abstract: The long-term stressful utilization of forests and grasslands has led to ecosystem degradation and C loss. Since the late 1970s China has launched six key national ecological restoration projects to protect its environment and restore degraded ecosystems. Here, we conducted a large-scale field investigation and a literature survey of biomass and soil C in China's forest, shrubland, and grassland ecosystems across the regions where the six projects were implemented (∼16% of the country's land area). We investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
368
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 616 publications
(381 citation statements)
references
References 27 publications
11
368
1
1
Order By: Relevance
“…Afforestation in semiarid areas has been proposed as an effective way for improving soil carbon accumulation and restoration of degraded ecosystems (Lu et al, ; Shi et al, ). Nevertheless, field studies have shown diverse response of carbon stock to afforestation, observing increase (Garcia‐Franco et al, ), decrease (Berthrong, Jobbágy, & Jackson, ; Parker, Subke, & Wookey, ), and no change (Yang, Luo, et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Afforestation in semiarid areas has been proposed as an effective way for improving soil carbon accumulation and restoration of degraded ecosystems (Lu et al, ; Shi et al, ). Nevertheless, field studies have shown diverse response of carbon stock to afforestation, observing increase (Garcia‐Franco et al, ), decrease (Berthrong, Jobbágy, & Jackson, ; Parker, Subke, & Wookey, ), and no change (Yang, Luo, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Drylands worldwide comprise approximately 47.2% of the terrestrial land surface and play a critical role in the global carbon cycle (Lal, ). However, the fragile semiarid ecosystem has been subjected to severe erosion and land degradation, due to the long‐term stressful excessive grazing and intensive cultivation (Lu et al, ). Afforestation has been widely launched to restore degraded ecosystems, and its effectiveness of soil erosion control and carbon sequestration was well documented in semiarid areas (Garcia‐Franco, Wiesmeier, Goberna, Martínez‐Mena, & Albaladejo, ; Lu et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations